The Registered Nurses amid COVID‐19 in Saudi Arabia: A descriptive phenomenological study - Jordan Tovera Salvador; Friyal Mubarak Alqahtani; Mu'taman Khalil Mohmoud Jarrar; Maria Abigail Cabiades Trinidad; Marc Oneel Castillo Alvarez; Kathlynn Buenaobra Sanchez; Ahrjaynes Balanag Rosario; Lilibeth Dela Victoria Reyes; Suzette Golez Cabonce; Darwin Damsani Agman; Sherien Ragab Dorgham (Wiley, 2023)
Abstract Aim To investigate the experiences of registered nurses' lived experiences in the Coronavirus Disease 2019 (COVID‐19) pandemic crisis in a government hospital in the Eastern Region of Saudi Arabia. Design Qualitative descriptive phenomenology. Methods Utilizing in‐depth interviews with twenty registered nurses with the use of purposive sampling from September to December 2020. Data was analyzed using Colaizzi methods, and a COREQ checklist was utilized to report the study's results. Results The participants' narratives generated three major themes, namely: 'one foot below the ground', 'the nightingale pledge'; and 'hope beyond COVID‐19'. The lived experiences of Registered Nurses throughout the pandemic brought by the COVID‐19 virus increase a person's understanding of the phenomenon under investigation and plan collective actions to improve the nurses' welfare. The unique challenges faced by Registered Nurses as they carry out their duties in a variety of healthcare settings can be better appreciated if their experiences are taken into account. Nursing administrations all around the world can use the findings of this research to create safeguards for their staff.